Efficacy and safety of cinobufacini capsules combined with oxaliplatin-based chemotherapy for advanced colorectal cancer: a human systematic review and meta-analysis - Wang, Jian; Gao, Qijia; Que, Yangming; Zheng, Dingting; Chen, Jianxin (Frontiers in Pharmacology, 2026)
BackgroundPatients with stage III–IV colorectal cancer (CRC) face poor prognosis due to metastases and limited treatment options. In China, cinobufacini capsules are widely used as a complementary medicine, but evidence for their clinical value remains insufficient.MethodsSystematic searches were conducted across seven databases, including Chinese National Knowledge Infrastructure (CNKI), WanFang Database, China Biological Medicine Database (CBM), PubMed, Embase, the Cochrane Library, and Web of Science, from their inception to 30 June 2025. The primary outcome was disease control rate (DCR), and the secondary outcomes were objective response rate (ORR), CD4+ T cells, carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9), carbohydrate antigen 125 (CA-125), and adverse reactions. This study strictly followed the PRISMA guidelines and used RevMan 5.3, Stata 15, and GRADEpro for data analysis.ResultsThe analysis showed that the combination therapy resulted in a higher DCR (RR = 1.18, 95% CI: 1.10–1.25; P < 0.0001) and ORR (RR = 1.40, 95% CI: 1.23–1.60; P < 0.0001), reduced CEA levels (WMD = −7.84, 95% CI: −10.43 to −5.23; P < 0.0001), CA-125 levels (WMD = −9.36, 95% CI: −12.80 to −5.92; P < 0.0001), and CA19-9 levels (WMD = −11.38, 95% CI: −12.66 to −10.11; P < 0.0001), as well as higher CD4+ T-cell levels (WMD = 2.74, 95% CI: 1.99–3.49; P < 0.0001). Additionally, the combination therapy could decrease the incidence of adverse reactions including leukocyte toxicity (RR = 0.59, 95% CI: 0.48–0.71; P < 0.0001), gastrointestinal toxicity (RR = 0.79, 95% CI: 0.62–0.99; P = 0.03), and myelosuppression (RR = 0.65, 95% CI: 0.46–0.92; P = 0.01). The level of evidence was assessed as moderate for DCR and low for ORR.ConclusionCinobufacini combined with oxaliplatin-based chemotherapy may enhance short-term efficacy, immune function, and safety in advanced CRC. However, due to limitations of existing RCTs, these findings should be interpreted cautiously, and further large-scale, high-quality trials are required.